Students’ Self-Assessment in Article Writing Class - Wisnu, Candra; Pradana, Satria Adi (Universitas Islam Negeri Raden Intan Lampung, 2020)
Nowadays, self-assessment has become one of the popular methods to measure the L2 students' abilities, especially in writing class, because the teachers start to know the advantages of self-assessment in class. However, the previous research shows that the application of self-assessment has several obstacles, such as the different language level proficiency, culture, and teachers' understanding. Moreover, there is still little research on self-assessment in Indonesia, which makes this method rarely used in classrooms. This research is aimed at finding out the students' understanding of self-assessment and the implementation of self-assessment. In this research, the researcher used a participatory photovoice narrative inquiry method to collect the data. Furthermore, the data of this study is taken by using photovoice and interviews. The participants were three fifth semester students in Article Writing class at the English Education Department of Universitas Sebelas Maret. This research is expected that using self-assessment in teaching and learning process can be beneficial for both students and teachers, such as knowing the students' abilities, development of students' writing skills, the increasing of students' participation in class, motivating the students to become more responsible for their learning process and the increase of students' interest in writing. The results add to the discussion on what makes the self-assessment method in writing class works successfully and have many advantages in classrooms.